Conocarpus erectus Leaf Extract for Green Synthesis of Silver Nanoparticles - Amjed Mirza Alsultani (Indonesian Journal of Chemistry, 2017)
Silver nanoparticles (SNPs) were synthesized by a green method using Conocarpus erectus leaves extract. Leaves were cleaned and used freshly then the extract was obtained by heating leaves in water for 15 min. Silver nitrate used as SNPs precursor and 5 mL of extract were added to silver ion solution at 80 °C and the growth of nanoparticle was monitored by electronic spectra at plasmon resonance absorption of SNPs, where the growth obeys sigmoidal kinetics. SNPs were characterized by SEM, XRD, FTIR, UV-vis absorption and fluorescence, and particle size was estimated. SEM reveals that the SNPs had spherical shape and particle size less than 100 nm. XRD analysis showed that only Ag phase was present and the estimated particle size was 20 nm. FTIR spectra analysis showed similarity of extract and SNPs, indicating the adsorption of active components of the extract on the high surface area of SNPs. Electronic absorption and fluorescence spectroscopy showed that plasmon absorption and fluorescence in the visible region were a characteristic feature of SNPs. Antibacterial activity examined against Escherichia coli and Staphylococcus aureus indicated that the inhibition zones were equal to 24 and 19 mm, respectively.